MEMINIMALKAN MISKONSEPSI PADA MATERI RANGKAIAN LISTRIK DENGAN PEMBELAJARAN PREDICT-OBSERVE-EXPLAIN - Mursalin (Universitas Negeri Malang, 2014)
Abstract: Minimizing Misconceptions on the Topic of Electric Circuits by Predict-Observe-Explain Learning. This pretest-posttest control group experiment was aimed to improve students' understanding of the concept and to minimize their misconceptions on the topic of electric circuits. The subjects were selected using cluster random sampling from high school students in Gorontalo. The instruments used to collect the data included pretest, posttest and questionnaires. The data were analyzed using t-test. The students' conception profiles were carried out using Certainty of Response Index (CRI) technique. The results show the significant difference in the posttest average and normalized gain average between the experimental and the control classes. The results are supported by the fact that misconceptions in the experimental class are smaller than those in the control class. The application of predict-observe-explain learning is effective to improve the understanding of the concept and minimize the misconceptions. Keywords: Predict-Observe-Explain Learning, concept understandings, misconception, electric circuits Abstrak: Meminimalkan Miskonsepsi pada Materi Rangkaian Listrik dengan Pembelajaran Predict-Observe-Predict. Artikel hasil penelitian ini memaparkan mengenai upaya meningkatkan pemahaman konsep dan meminimalkan miskonsepsi pada materi rangkaian listrik dengan menggunakan model pembelajaran Predict-Observe-Explain (POE). Penelitian dilakukan secara eksperimen dengan pretest-posttest control group design. Subyek penelitian ditentukan dengan teknik cluster random sampling dari siswa SMA kelas X suatu sekolah di Kota Gorontalo. Analisis data dilakukan dengan uji beda rerata gain ternormalisasi antara kelas eksperimen dan kelas kontrol, dan profil konsepsi siswa dianalisis dengan teknik Certainty of Response Index. Hasil penelitian mengungkap bahwa penerapan model pembelajaran POE efektif meningkatkan pemahaman konsep dan meminimalkan miskonsepsi siswa. Kata kunci: Predict-Observe-Explain Learning, pemahaman konsep, miskonsepsi, rangkaian listrik